Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2140/apde.2016.9.1772
|View full text |Cite
|
Sign up to set email alerts
|

Estimates for radial solutions of the homogeneous Landau equation with Coulomb potential

Abstract: Motivated by the question of existence of global solutions, we obtain pointwise upper bounds for radially symmetric and monotone solutions to the homogeneous Landau equation with Coulomb potential. The estimates say that blow up in the L ∞ (R 3 )-norm at a finite time T can occur only if the L 3/2 (R 3 )-norm of the solution concentrates for times close to T . The bounds are obtained using the comparison principle for the Landau equation and for the associated mass function. This method provides long-time exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…The fact that neither (7) not (8) can be proven at the moment is rather unsatisfactory. And consequently the results stated in Theorem 2 should be viewed as conditional.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that neither (7) not (8) can be proven at the moment is rather unsatisfactory. And consequently the results stated in Theorem 2 should be viewed as conditional.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the first author and collaborator showed in [8] global in time existence of smooth and bounded radial and monotone decreasing solutions to (1) for initial data that have finite mass, energy and entropy. This last result puts in evidence how solutions to a non-linear equation with a non-local diffusivity such as a[u] behave drastically different from (and better than) Keller-Segel or semilinear heat equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the set of initial data for which this theory is valid has been improved by Carrapatoso and Mischler [9] via a linearization method.Recently the first author and Guillen have shown, for the Coulomb case, global in time existence of classical solution for a modified isotropic homogeneous Landau equationin the case of radially symmetric (but no smallness assumptions!) initial data 55 [22]. Moreover, using the theory of A p weights, they showed that solutions to the original Landau equations with general initial data for γ > −2 have an instantaneous regularization which does not deteriorate as time increases, with bounds that only depend on the physical quantities, mass, momentum and energy [21].…”
mentioning
confidence: 99%
“…in the case of radially symmetric (but no smallness assumptions!) initial data 55 [22]. Moreover, using the theory of A p weights, they showed that solutions to the original Landau equations with general initial data for γ > −2 have an instantaneous regularization which does not deteriorate as time increases, with bounds that only depend on the physical quantities, mass, momentum and energy [21].…”
mentioning
confidence: 99%